The role of vigilance and alarm calling in the red junglefowl, Gallus gallus - Kazara, HK (2019)
Vigilance and alarm calling are considered exclusively anti-predator behaviours. However recent work suggests they may have other functions. My thesis explores the role of vigilance and alarm calling in red junglefowl, Gallus gallus. Male fowl are more vigilant than females and produce male-specific alarm calls for aerial predators. Chapter 2 tested hypotheses for male vigilance and aerial alarm calling by manipulating group size and sex ratio. Vigilance and alarm calling generally increased as groups became more female-biased, potentially reflecting compensation for reduced female vigilance. Chapter 3 explored how male vigilance and aerial alarm calling correlated with measures of male pre- and post-copulatory mating success; finding that more vigilant males and males that produced more alarm calls had higher mating success. One explanation for the link between male vigilance and alarm calling and mating success is that males invest more to protect their sexual partners to increase the survival of offspring that they may have sired. Chapter 4 tested this by experimentally manipulating male paternity confidence and mating success by allowing or preventing sexual access to a female in the presence or absence of male competitors. Males invested more in vigilance and alarm calling when they had sexual access to a female, regardless of the level of competition, which suggests that male investment is related to mating success per se. Finally, Chapter 5 considered the role of vigilance in females using two approaches. First, in mixed-sex groups females were three times less vigilant than males. Second, I examined whether female vigilance could play a role in foraging by allowing an individual to gather information on food location by watching a conspecific. I found no evidence that vigilance enables foraging females to gather information. Collectively, these results suggest that vigilance and alarm calling are linked to mating behaviour in male fowl.